Sistem RGEC Dalam Analisis Tingkat Kesehatan Bank Digital Yang Terdaftar Di BEI Periode 2019-2022 - Helmi, Aristo Yonitus; Kristianto, Aloysius Hari (Fakultas Ekonomi Universitas KH. A. Wahab Hasbullah Tambakberas Jombang, 2024)
The development of information technology has transformed the landscape of banking services, leading to the emergence of digital banks as a promising alternative. Digital banks offer banking services without physical presence, relying on digital platforms for all transactions and communications. However, with rapid growth, digital banks face various challenges, including stringent regulations, increased competition, and effective risk management. This study aims to analyze the financial health of digital banks in Indonesia during the period 2019-2022, focusing on six digital banks listed on the Indonesia Stock Exchange. The RGEC method is used to evaluate key aspects such as risk profile, corporate governance, earnings, and capital. The results of the analysis show variations in the financial performance of digital banks, with some banks showing consistent growth while others experiencing fluctuations. However, overall, digital banks demonstrate relatively healthy performance in managing risks and maintaining capital adequacy. By understanding the factors influencing the financial health of digital banks, this study provides valuable insights for investors, regulators, and other stakeholders in understanding the dynamics of the digital banking industry in Indonesia.